Sustainable Acoustic Insulation: Sound Transmission Loss in Fish Scale-Epoxy Composite Materials - Woon Li Ying; Sanusi, Shahmir Hayyan (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The rapid development in urbanization and industrial activities has led to a significant increased in noise pollution, raising serious concern for both public health and environmental. While conventional acoustic material such as synthetic fibres are effective in reducing noise level, but their non-biodegradable and potentially hazardous nature has prompted interest in more sustainable alternatives. This study investigated the sound transmission loss (STL) characteristics of fish scale-reinforced epoxy composites as an eco-friendly solution for noise control applications. Fish scales were chemically treated and processed into granule and powdered fish scale, then incorporated into epoxy resin at different fish scale ratios, thickness, and structural arrangements. The STL performance of the resulting composite samples was evaluated using an impedance tube across a frequency range of 70 Hz to 6000 Hz. Scanning Electron Microscopy (SEM) was also employed to examine internal morphology and correlate structural features with sound insulation behavior. The results demonstrated that the incorporation of fish scales, especially in powdered form at optimized ratios, significantly enhanced the STL of composite panels compared to conventional PVC and pure epoxy panels. The study emphasized the importance of optimizing both filler loading and sample thickness, as excessive filler content was found to increase rigidity and negatively impact sound insulation. These findings highlighted the potential of fish scale-reinforced composites as sustainable, high-performance materials for sound insulation, contributing to waste reduction and supporting the advancement of green material development in architectural and industrial acoustic applications.